2023
DOI: 10.1093/narcan/zcad019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms protecting centromeres from self-sabotage and implications for cancer therapy

Abstract: Centromeres play a crucial role in DNA segregation by mediating the cohesion and separation of sister chromatids during cell division. Centromere dysfunction, breakage or compromised centromeric integrity can generate aneuploidies and chromosomal instability, which are cellular features associated with cancer initiation and progression. Maintaining centromere integrity is thus essential for genome stability. However, the centromere itself is prone to DNA breaks, likely due to its intrinsically fragile nature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Interestingly, the chromosome 18 features found by our study were not located around previously indicated genes along the long arm of chromosome 18 but rather located around centromeres. Centromere dysfunction, breakage, or compromised centromeric integrity has been reported to be linked to cancer initiation and progression as it leads to chromosomal instability and aneuploidies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the chromosome 18 features found by our study were not located around previously indicated genes along the long arm of chromosome 18 but rather located around centromeres. Centromere dysfunction, breakage, or compromised centromeric integrity has been reported to be linked to cancer initiation and progression as it leads to chromosomal instability and aneuploidies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In situations where cells undergo premature entry into mitosis while having damaged and under-replicated genomes, one would expect late-replicating regions such as centromeric DNA to remain incompletely replicated despite cell cycle progression. Notably, proteins implicated in DNA repair and replication stress pathways may become enriched during centromeric replication 41 , as these genomic loci are fragile and challenging to replicate. The DNA2 helicase/nuclease, a putative substrate of CDK1 42 , has high affinity for centromeric DNA 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Nassar et al. bring insight into the protection mechanisms essential to maintain centromeres and how these mechanisms may be exploited for cancer selective treatment options ( 50 ). Telomeres are a unique genomic structure that depends on telomerase, a specialized reverse transcriptase required for telomere maintenance.…”
mentioning
confidence: 99%